THE ATTITUDES AND EXPERIENCES OF THE INTERNET AND SOCIAL MEDIA USERS IN SERBIA - Đurić, Slađana (Journal of process management and new technologies, 2019)
The Internet and its platforms and services became very important tool for marketers in creating online advertising campaigns and for establishing and deepening relationship with their customers. Online marketing and creating opened, direct and transparent relationship with every individual customer is very powerful instrument in promotion of companies and significantly increases the chances of gaining competitive advantage. The purpose of this research paperwork was to get the knowledge about actual attitudes, opinions and experiences of Internet users in Serbia and to collect data that can be used for online campaigns planning. Various analysis were undertaken in order to present the potential of Internet and social media for marketers, companies and entrepreneurs in planning and implementing their online presence.